Ground settlement due to tunnelling and effect of groundwater table variation and superstructure on the tunnel - Md. Rehan Sadique; Ibraheem Rais; Osama Iqbal; Syed Muhammad Ibrahim (Discover Civil Engineering)
Abstract Underground structures, such as tunnels for mass rapid transit systems, automobile and railway tunnels, and underground gas and petroleum storage facilities, play a critical role in transportation and utility networks. The objective of this study is to examine the response of a tunnel to a static load using both experimental and numerical techniques. The effects of excavation, construction of the superstructure, and groundwater table in the vicinity of existing tunnels have been investigated. A physical soil-tunnel model of 1 m × 1.3 m × 1 m has been developed in the lab. An aluminium tunnel liner of diameter 22.5 cm and two different gauge of thicknesses (22 gauge and 26 gauge) have been explicitly installed. The results obtained from the experiment, i.e., surface settlement, have been compared with numerical analysis through a finite element technique. Furthermore, total stress and shear stress have been obtained through the numerical analysis. A full-scale numerical model, replicating actual field conditions, has also been analyzed. The results show that an aluminium liner with a 22-gauge thickness causes maximum surface settlement at the center of the soil-tunnel model. Moreover, the heaving of soil occurs when the groundwater table rises above the crown of the tunnel. This study is significant as it provides critical insights into the behavior of tunnels under static loads and the impact of groundwater levels, offering valuable guidance for designing safer and more resilient underground structures.